In the Service of their Homeland and Themselves: The U.S. Women's Club in Costa Rica 1945–1980. Issue 2 (4th September 2017) - Shragai, Atalia
Abstract: This article examines the Women's Club of Costa Rica/Club de Mujeres de Costa Rica (WCCR), an English-speaking and U.S.-oriented civic organization in Costa Rica, from its establishment in 1940 through the 1970s. Based on oral histories with club members and the WCCR primary sources, the article considers the WCCR not as a foreign enclave but rather as a civic institution that functioned at the borderland of homeland (the United States) and country of residence (Costa Rica), as well as on the borderland of formal and nonformal U.S. activities in Cold War Costa Rica. I argue that from the 1950s to the 1970s, the WCCR was a significant factor in shaping the national, cultural, and gendered identifications of U.S. women in Costa Rica. Although it was a civic, independent institution, its members took it upon themselves to serve the interest of the United States as a way of forging their identity and legitimizing their presence—and the U.S. presence—in Costa Rica. The article thus offers a rich perspective for examining the intersection of U.S. empire, gender, and civic institutions. However, I argue that what might be perceived as a conservative club engaged in traditionally feminine activities and patriotic propaganda, served as a mechanism for liberation and empowerment for many of its members.